Transforming Refugee Management in the Context of Sustainable International Development - Fauzan, Fauzan; Helmi, Helmi; Harza, Zulkifli; Oktavia, Sri (European Publisher, 2019)
The increasing mobility of refugees due to conflict, persecution or other generalized violence has become a phenomenon worldwide. Both states and the Nations High Commissioner for Refugees (UNHCR) have faced challenges in managing refugees sustainably. This research is intended to analyze the limitation of states in the EU and ASEAN region as well as the UNHCR challenges in managing refugees. The methodology used is a quantitative study through a statistical descriptive analysis from secondary sources and literature reviews. The results show that states are reluctant to receive new refugees since they could harm the state’s sovereignty. Besides, the UNHCR has also faced a challenge by not being able to resettle more refugees to third countries due to the reduction of quotas of resettlement. Since refugee is a complex issue involving not only states and UNHCR, partnership with the international organization including private sectors is required to provide alternative solutions, particularly through a partnership with TNCs. The role of TNCs would be essential since they have supply chains across the globe for market expansion and capacity building for refugees through the reallocation of the CSR programs. The SDGs have also acknowledged partnership to become a specific goal of 17 to be achieved in 2030, along with other global initiatives. It concludes that TNCs could play a role in refugee management by providing skill enhancement for refugees through CSR programs to enter labor opportunities in the future.